2017
DOI: 10.1186/s12889-017-4163-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability via Active Garden Education (SAGE): results from two feasibility pilot studies

Abstract: BackgroundLow physical activity (PA) and fruit and vegetable (F&V) consumption in early childhood are continued public health challenges. This manuscript describes outcomes from two pilot studies for Sustainability via Active Garden Education (SAGE), a program designed to increase PA and F&V consumption among 3 to 5 year old children.MethodsSAGE was developed using community-based participatory research (CBPR) and delivered to children (N = 89) in early care and education centers (ECEC, N = 6) in two US cities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 49 publications
2
32
1
Order By: Relevance
“…Using sample size simulation tools for cluster-randomized trials along with intraclass correlation (ICC, an index of within-ECEC clustering) and variance estimates derived from our pilot data, we found that a complete-case sample size of 280 child-caregiver dyads yielded estimated power > 0.83 to detect small changes of 2.75 min/h MVPA and 4.50 min/total physical activity under relatively low clustering (ICCs = 0.11, 0.19) and modest changes (4.25 min/h MVPA, 6.50 min/ h total physical activity) under strong clustering (ICCs = 0.55, 0.60) at α = 0.05. These differences are smaller than those seen in our pilot data (MVPA differences = 3 min/h, 11 min/h; total physical activity differences = 5 min/h, 12 min/h) [24]. Given ICC and variance estimates derived from our pilot data, this sample size also afforded power > 0.85 to detect differences in combined fruit and vegetable consumption of 1.20 servings/day.…”
Section: Sample Size Calculationcontrasting
confidence: 52%
See 4 more Smart Citations
“…Using sample size simulation tools for cluster-randomized trials along with intraclass correlation (ICC, an index of within-ECEC clustering) and variance estimates derived from our pilot data, we found that a complete-case sample size of 280 child-caregiver dyads yielded estimated power > 0.83 to detect small changes of 2.75 min/h MVPA and 4.50 min/total physical activity under relatively low clustering (ICCs = 0.11, 0.19) and modest changes (4.25 min/h MVPA, 6.50 min/ h total physical activity) under strong clustering (ICCs = 0.55, 0.60) at α = 0.05. These differences are smaller than those seen in our pilot data (MVPA differences = 3 min/h, 11 min/h; total physical activity differences = 5 min/h, 12 min/h) [24]. Given ICC and variance estimates derived from our pilot data, this sample size also afforded power > 0.85 to detect differences in combined fruit and vegetable consumption of 1.20 servings/day.…”
Section: Sample Size Calculationcontrasting
confidence: 52%
“…Collaborative intervention development meant that the intervention and comparison group strategies, materials and protocols were meaningful and relevant for not only testing a novel intervention strategy to move the science forward but also bestowing great benefit to the community who was served by SAGE: easy to implement, fun for everyone, and an engaging learning experience. In addition, including ECEC staff in the pilot studies developing SAGE helped to infuse the importance of meeting educational standards into the curriculum, in addition to meeting federal guidelines for health behaviors in young children [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations